O064 Early follow-up quality of life and mental health of patients with congenital vascular malformations cared for in a multi-disciplinary specialist center. (22nd July 2022) - Pang, C; Nisbet, R; Gibson, M; Evans, N; Khalifa, M; Papadopoulou, A; Tsui, J; Hamilton, G; Brookes, J; Lim, CS
Abstract: Introduction: To evaluate the early follow-up quality of life (QoL), pain and mental health of patients with congenital vascular malformation (CVM) receiving care by a single multi-disciplinary specialist centre Methods: All patients with CVM who received care (supportive treatment only, open surgery, targeted pharmacological therapy, embolosclerotherapy), and had follow-up, between 1 February 2018 and 31 January 2020 were included. The health-related QoL, pain, and mental health were assessed with validated questionnaires: SF-36, VAS-P and HADS. The CVM were categorized into types – low-flow (LFVM) and high-flow (HFVM), and anatomical locations. Paired t-test was used for all analyses. Differences were considered significant at P<0.05. Results: 110 patients (85 LFVM and 25 HFVM) with a mean age of 36.9 years were included. Significant improvement was found in the bodily pain domain of SF-36 and VAS-P (both P = 0.01) in all patients. However, only patients with HFVM reported significant improvement in the bodily pain domain of SF-36 (P=0.002) and VAS-P (P = 0.02). Patients who received supportive treatment only reported significant improvement in mental health (P=0.004) and social functioning (P=0.03) domains of SF-36. Meanwhile, patients treated with embolosclerotherapy reported significant improvement only in VAS-P (P=0.02). Patients who received targeted pharmacological therapy reported no significant early changes. Conclusion: The effects of care on early follow-up QoL, pain and mental health of patients with CVM were heterogenous. Future research is required to understand the various factors that affect the QoL and mental health of these patients, as well as the holistic approaches to manage them. Take-home message: The effects of care on early follow-up QoL, pain and mental health of patients with CVM were heterogenous. Future research is required to understand the various factors that affect the QoL and mental health of these patients, as well as the holistic approaches to manage them.